Cigarette smoke enhances oncogene addiction to c‐MET and desensitizes EGFR‐expressing non‐small cell lung cancer to EGFR TKIs. Issue 5 (14th April 2018) - Tu, Chih‐Yen; Cheng, Fang‐Ju; Chen, Chuan‐Mu; Wang, Shu‐Ling; Hsiao, Yu‐Chun; Chen, Chia‐Hung; Hsia, Te‐Chun; He, Yu‐Hao; Wang, Bo‐Wei; Hsieh, I‐Shan; Yeh, Yi‐Lun; Tang, Chih‐Hsin; et al.
Abstract : Cigarette smoking is one of the leading risks for lung cancer and is associated with the insensitivity of non‐small cell lung cancer (NSCLC) to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs). However, it remains undetermined whether and how cigarette smoke affects the therapeutic efficacy of EGFR TKIs. In this study, our data showed that chronic exposure to cigarette smoke extract (CSE) or tobacco smoke‐derived carcinogen benzo[α]pyrene, B[α]P, but not nicotine‐derived nitrosamine ketone (NNK), reduced the sensitivity of wild‐type EGFR‐expressing NSCLC cells to EGFR TKIs. Treatment with TKIs almost abolished EGFR tyrosine kinase activity but did not show an inhibitory effect on downstream Akt and ERK pathways in B[α]P‐treated NSCLC cells. CSE and B[α]P transcriptionally upregulate c‐MET and activate its downstream Akt pathway, which is not inhibited by EGFR TKIs. Silencing of c‐MET reduces B[α]P‐induced Akt activation. The CSE‐treated NSCLC cells are sensitive to the c‐MET inhibitor crizotinib. These findings suggest that cigarette smoke augments oncogene addiction to c‐MET in NSCLC cells and that MET inhibitors may show clinical benefits for lung cancer patients with a smoking history. Abstract : Patients with non‐ small cell lung cancer ((NSCLC) with a history of smoking show increased resistance to EGFR TKIs. However, the causal relationship between cigarette smoke and the therapeutic efficacy of EGFR TKIs remains undetermined. Here, our data demonstrate that chronic exposure to cigarette smoke extract or the tobacco smoke‐derived carcinogen benzo[α]pyrene (B[α]P) reduce NSCLC sensitivity to EGFR TKI through c‐MET upregulation and activation.